Magnetic properties of Ndfe11ti and YFe11ti, from experiment and theory. (1st January 2023) - Herper, Heike C.; Skokov, Konstantin P.; Ener, Semih; Thunström, Patrik; Diop, Léopold V.B.; Gutfleisch, Oliver; Eriksson, Olle
Graphical abstract: Abstract: NdFe 11 Ti and YFe 11 Ti serve as prototypes for rare-earth (RE) lean or REfree magnets with the ThMn 12 -type structure. Although NdFe 11 Ti has been studied for a long time the origin of its complex magnetism at low temperature is so far not well-understood. We present a comprehensive theoretical and experimental study of the magnetic properties of NdFe 11 Ti and RE-free YFe 11 Ti to elucidate the influence of the 4 f electrons. The partially localized 4 f electrons of Nd are the driving force behind the complex behavior of the magnetocrystalline anisotropy which changes from cone to uniaxial above 170 dK. The spontaneous magnetization and the five leading anisotropy constants were determined from high-quality single crystal samples over a wide temperature range using field dependencies of magnetization measured along the principle crystallographic directions. The experimental data are compared with density functional theory combined with a Hartree-Fock correction (+U) and an approximate dynamical mean-field theory.